BIOECOLOGY OF SMALL MAMMALS IN THE VICINITY OF THE CITY OF NUKUS - Zholdasbaeva, E.K.; Turekeeva, A.J. (SCIENCE and SOCIETY, 2026)
This article presents information on the lifestyle, distribution range, reproduction, feeding habits, and observed dynamic changes of mammals in the vicinity of Nukus city.